Pembangunan modul pembelajaran webquest pendidikan kesihatan untuk guru pelatih murid bermasalah pembelajaran / Alijah Ujang - Alijah, Ujang (2016)
This study was aimed at developing a WebQuest Health Education (WQPKes) learning module for trainee teachers of pupils with learning difficulties in primary schools. The Design and Development research methodology introduced by Richey dan Klein (2014) was used in this study involving three phases. Data from the first phase of needs analysis were collected through a questionnaire distributed to 63 trainee teachers in the Learning Difficulties Special Education Program(PKMP) using purposive sampling. Findings from the closed questions were analyzed by percentage while the open-ended responses were subjected to thematic analysis. The data from the second phase were obtained through the Fuzzy Delphi technique by 20 experts in Health Education, Special Education and also Information and Communications Technology. Analysis relied on the experts’ responses to the questionnaire based on a five-point Likert linguistic scale. The threshold(d) value was calculated to determine the expert consensus on all questionnaire items. The phase two of development involved reviewing the lesson plan; “Healthy Lifestyle” according to the WebQuest procedure using elements like eating habits of learning disabled students, medicine, drugs and nicotine, exercise and recreation, rest,recuperation and leisure as subtopic. The guided projects and problem solving, task-analysis, and graphic organizer were used as learning techniques. Internet information search, face to face discussion, and simulations as learning activities while role playing and creating powerpoint as an exercise. The phase three or module usability evaluation was done through retrospective on 10 PKMP trainee teachers who had used the WQPKes learning module with two lecturers as facilitators. Semi structured interview responses were analyzed thematically. The findings show that there was a need to develop a WQPKes learning module for trainee teachers in the PKMP program. The majority of trainee teachers agree that Health Education was important to be learned by learning difficulties pupils in primary schools and be taught during teacher training. The majority of trainee teachers also agree that the WQPKes module be developed with cleanliness, food and diet as health education issues and module contents. Findings in the need analysis phase support the development of a WQPKes learning module for trainee teachers. The findings in phase two of design study show that the experts achieved unanimous consensus that the threshold value (d ) ≤ 0.2 exceeded 75% for the suitability of items in the learning module. The findings of the development phase suggested the need of improvement. The results of module usability evaluation show that the WQPKes learning module is appropriate for trainee teachers of pupils with learning difficulties. They were satisfied with the learning technique, learning activities and exercises prepared in the WQPKes learning module. This learning module strength lies in its ability to enhance knowledge and skills, assist the education of trainee teachers, suitable, easy to follow and interesting, therefore it is potential for the Ministry of Education Malaysia, Teacher Education Institutes in Malaysia (IPGM), lecturers in IPG and student teachers in the PKMP program to use.